Dietetic value of nuts - Smith, Marjory C. (My University, 1904)
Introduction: Thought the use of nuts not only in this country but in foreign countries has attained considerable proporitions, if a careful study of their food qualities were made it would lead to their largely increased consumption. Nuts have a high nutrative value and with the cheapness by which they may be produced it is somewhat rernerkable that they have received so little attention as food. This may be accounted for to some extent by the abundance and cheapness of cereal products which have thus far been in sufficient qualities to meet the general demand of such food. Cereals are almost certain crops. Because land is cheap and plentiful. We have not been forced to seek food from less reliable sources. As the world becomes more densely populated crops, will have to be chosen that produce more food to the acre than do the grains. So it will not be long before nuts hold a high place in the diet. Nuts and fruits without doubt constituted the food of primative. There is now a class of people called the Fruitarians whose diet is composed of fruits and nuts alone. They claim that they have better health and are happier then when their diet was composed largely of animal food.
Citation: Smith, Marjory C. Dietetic value of nuts. Senior thesis, Kansas State Agricultural College, 1904.
Morse Department of Special Collections
Keywords: Nuts; Nutrition; Types of Nuts; Applications of Nuts; Theses